124 CARCINOMATOUS MENINGITIS ARISING FROM PRIMARY ESOPHAGEAL ADENOCARCINOMA: AN UNCOMMON COMPLICATION. Issue 1 (1st January 2007) - Haq, S.; Sanders, S.; Saghier, S.
Abstract : Background: Carcinomatous meningitis is the invasion of neoplastic cells into the leptomeninges. The primary tumors that typically cause leptomeningeal metastasis include lung cancer, breast cancer, leukemia, lymphoma, and melanoma. We describe an interesting case of neoplastic meningitis caused by a poorly differentiated esophageal adenocarcinoma, which is an uncommon complication of this particular malignancy. Case Presentation: A 56-year-old white male presented to the ER with new onset of tonic-clonic seizure along with a 1-week history of headaches and low-grade fever. Past medical history consisted of esophageal carcinoma diagnosed 1 year ago, which was treated with chemotherapy and radiation. Physical examination was remarkable for neck stiffness and photophobia. Admission laboratory tests showed only leukocytosis (13, 000). Serum and urine drug screens were negative. A CT scan and MRI of the brain were unremarkable. CSF studies were nonspecific. Cultures of blood and CSF were all negative. Cytology of the CSF revealed malignant cells consistent with poorly differentiated adenocarcinoma of the esophagus. Oncology was consulted and intrathecal chemotherapy (methotrexate) was begun via ommaya reservoir. The patient responded well to the chemotherapy with resolution of his symptoms. He was discharged home in stable condition. Discussion: This case report of carcinomatous meningitis from previously treated primary esophageal adenocarcinoma is one of the few reported in the literature. The mechanism of spread may be by direct invasion of malignant cells or by hematogenous seeding. The clinical course is relentlessly progressive despite treatment. The overall prognosis is poor with median survival rates of 3 to 6 months in patients receiving treatment versus 4 to 6 weeks in patients without treatment. Carcinomatous meningitis has become an increasingly important late complication in oncology since patients survive longer and develop brain metastases and because newer chemotherapeutic agents used to treat primary tumors may not penetrate the blood-brain barrier.